Social capital in a diverse Malaysia: enhancing bonding, bridging, and linking for greater social cohesion - Zaini Othman (Penerbit Universiti Kebangsaan Malaysia, 2025)
This article explores the role of social capital in fostering social cohesion within Malaysia's multicultural society, focusing on three key dimensions: bonding, bridging, and linking social capital. The study aims to understand how these forms contribute to community resilience, inclusive development, and national unity. Using a qualitative approach, the research incorporates a literature review, case studies, and empirical evidence. Bonding social capital is examined through its role in strengthening intra-group ties, preserving cultural identity, and providing social support. Bridging social capital is assessed in terms of its potential to encourage inter-ethnic cooperation, while linking social capital is analysed for its capacity to connect marginalized groups to institutional resources, thus promoting social mobility. The findings highlight the importance of nurturing all three types of social capital to address socio-economic disparities and historical divisions. The article also identifies barriers to effective social capital development, including entrenched ethnic divisions and economic inequality. In conclusion, the study advocates for targeted policy interventions to enhance social capital, ultimately fostering greater social cohesion and equity in Malaysia.